2014
DOI: 10.4293/108680813x13753907292755
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Dorsal Sympathectomy for Upper Limb Buerger's Disease

Abstract: Background and Objectives:Thromboangiitis obliterans is a common peripheral vascular disease in India. This study was conducted to assess the efficacy of thoracoscopic dorsal sympathectomy as a treatment for Buerger disease of the upper extremities.Methods:Thirty thoracoscopic dorsal sympathectomies (17 left- and 13 right-sided) were performed in a tertiary medical center in 5 women and 20 men (mean age, 41 years) between July 2010 and February 2013.Results:The mean operative time was 30 minutes, and the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Complete healing was achieved in 61.9 % of the iloprost group and 41 % of the lumbar sympathectomy group at 4 weeks (P = .012) and in 85.3 versus 52.3 %, respectively, at 24 weeks (P G .001) [169]. Kothari et al recently reported that thoracoscopic dorsal sympathectomy reduces pain in patients with upper limb involvement in a recent case series of 25 TAO patients from India [170].…”
Section: Lumbar or Thoracic Sympathectomymentioning
confidence: 99%
“…Complete healing was achieved in 61.9 % of the iloprost group and 41 % of the lumbar sympathectomy group at 4 weeks (P = .012) and in 85.3 versus 52.3 %, respectively, at 24 weeks (P G .001) [169]. Kothari et al recently reported that thoracoscopic dorsal sympathectomy reduces pain in patients with upper limb involvement in a recent case series of 25 TAO patients from India [170].…”
Section: Lumbar or Thoracic Sympathectomymentioning
confidence: 99%
“…The limb involved is often characterized by skin chill, reduced or undetectable pulse, numbness, and intermittent claudication accompanied by migratory thrombophlebitis or superficial phlebitis. Ulcers or necrosis appear in serious cases (Kothari et al, 2014;Liu et al, 2014a;Yuan et al, 2014). As a vascular occlusive disease, the main pathogenesis of TO is ischemia and hypoxia.…”
Section: Introductionmentioning
confidence: 99%